1997
DOI: 10.1023/a:1018450204980
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Matrix metalloproteinases (MMPs) play an important regulatory role in tissue morphogenesis, cell differentiation, tumor invasion and metastasis. Several authors have reported a direct correlation between the production of 72 kDa (MMP-2) and 92 kDa (MMP-9) type IV collagenases/gelatinases and the metastatic potential of cancer cells. Recently, we have identified the expression of both MMP-2 and MMP-9 in primary cultures of human giant cell tumor (GCT) of bone in vitro, and in tissue extracts in vivo. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our results are consistent with other studies that demonstrated the stromal cells of GCT are stimulated by local cytokines such as tumor necrosis factor alpha (TNFα) and interleukin-1 (IL-1) to express and produce several angiogenic and proteolytic factors, including vascular endothelial growth factor (VEGF), MMP-3, and MMP-9 [39–43]. Rao et al showed that media from fresh GCT specimens activated MMP-9 in late-passaged stromal cells [31]. …”
Section: Discussionsupporting
confidence: 83%
“…Our results are consistent with other studies that demonstrated the stromal cells of GCT are stimulated by local cytokines such as tumor necrosis factor alpha (TNFα) and interleukin-1 (IL-1) to express and produce several angiogenic and proteolytic factors, including vascular endothelial growth factor (VEGF), MMP-3, and MMP-9 [39–43]. Rao et al showed that media from fresh GCT specimens activated MMP-9 in late-passaged stromal cells [31]. …”
Section: Discussionsupporting
confidence: 83%
“…MMP-9 (matrix metalloproteinases-9) is one of the MMPs, a family of the prominent enzymes that degrade different components of the extracellular matrix [ 33 ]. Among the various MMPs, MMP-2 (gelatinase A) and MMP-9 (gelatinase B) may play a significant role in tumor progression and invasion in GCT [ 20 , 34 ]. Bone matrix destruction via type-I collagen degradation by osteoclasts leaves behind denatured type-I collagen (gelatin), which MMP-2 and MMP-9 degrade, leading to osteolysis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathway analysis also identified several subpathways that were affected, to a statistically significant extent, in the GCTB patients—including the inhibition of the matrix metalloproteases pathway (data not shown). A number of studies have shown that MMPs are also synthesized in tumor cells to regulate tumor invasion and metastasis in malignant tumors [ 34 , 38 , 39 ]. MMP1 and a disintegrin-like metalloproteinase with thrombospondin motifs 1 (ADAMTS1), shed epidermal growth factor (EGF)-like ligands to suppress OPG, indirectly leading to osteoclastogenesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, MMPs at the metastastic sites are expressed at a higher level compared to corresponding primary tumors 73. MMP-9 is expressed in giant cell tumor of bone and because normal cells such as fibroblasts do not synthesize MMP-9, the production of MMP-9 may be important for the migration of cells into the blood stream, lymphatic vessels or adjacent normal tissues 74. MMP-13 has been reported to accelerate bone remodeling and promotes proliferation while inhibiting apoptosis in human osteoblast-like cells, and its expression is upregulated in giant cell tumor of bone 75-77.…”
Section: Discussionmentioning
confidence: 99%